The Effectiveness of Interactive E-Modules as Learning Media to Train Visual Spatial Intelligence in Chemical Bond Material - Fatmawati, Ria; Sukarmin, Sukarmin (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study aims to determine the effectiveness of interactive e-module that train students' visual intelligence on chemical bond material. Chemical bond is one of the high school chemistry materials that has basic concepts that must be mastered in order to understand other chemistry topics and abstracts require the ability to understand what must be stimulated. This study was compiled based on the 4D research and development (R&D) model. The subjects and population of this study were students of class XI IPA at SMAN 12 Surabaya. The effectiveness of the review of cognitive domain tests and spatial visual intelligence tests before and after the use of a 3D visualialization base interactive e-module. The analysis of this study used N-gain and normality statistical tests until the data were normally distributed. The effectiveness of the media was stated to be very effective with an N-Gain score on the cognitive test of 0.8 in the high category and the spatial visual intelligence test of 0.8 in the high category which shows the relationship between cognitive domain tests and visual spatial tests can improve understanding of chemical bond material. The results of the research show that it is feasible to implement